Chromatin accessibility landscape of stromal subpopulations reveals distinct metabolic and inflammatory features of porcine subcutaneous and visceral adipose tissue - Sun, Wenyang; Zhang, Tinghuan; Hu, Silu; Tang, Qianzi; Long, Xi; Yang, Xu; Gun, Shuangbao; Chen, Lei (PeerJ, 2022)
Background Fat accumulation in visceral adipose tissue (VAT) confers increased risk for metabolic disorders of obesity, whereas accumulation of subcutaneous adipose tissue (SAT) is associated with lower risk and may be protective. Previous studies have shed light on the gene expression profile differences between SAT and VAT; however, the chromatin accessibility landscape differences and how the cis-regulatory elements govern gene expression changes between SAT and VAT are unknown. Methods Pig were used to characterize the differences in chromatin accessibility between the two adipose depots-derived stromal vascular fractions (SVFs) using DNase-sequencing (DNase-seq). Using integrated data from DNase-seq, H3K27ac ChIP-sequencing (ChIP-seq), and RNA-sequencing (RNA-seq), we investigated how the regulatory locus complexity regulated gene expression changes between SAT and VAT and the possible impact that these changes may have on the different biological functions of these two adipose depots. Results SVFs form SAT and VAT (S-SVF and V-SVF) have differential chromatin accessibility landscapes. The differential DNase I hypersensitive site (DHS)-associated genes, which indicate dynamic chromatin accessibility, were mainly involved in metabolic processes and inflammatory responses. Additionally, the Krüppel-like factor family of transcription factors were enriched in the differential DHSs. Furthermore, the chromatin accessibility data were highly associated with differential gene expression as indicated using H3K27ac ChIP-seq and RNA-seq data, supporting the validity of the differential gene expression determined using DNase-seq. Moreover, by combining epigenetic and transcriptomic data, we identified two candidate genes, NR1D1 and CRYM, could be crucial to regulate distinct metabolic and inflammatory characteristics between SAT and VAT. Together, these results uncovered differences in the transcription regulatory network and enriched the mechanistic understanding of the different biological functions between SAT and VAT.
Keywords: Subcutaneous adipose tissues; Visceral adipose tissues; Stromal vascular fraction; Chromatin accessibility; Pig